Phenomena of Color and Sound in the Autumn Lyrics by Georg Trakl - Elizaveta V. Sokolova (Studia Litterarum)
The autumn poems of the Austrian poet Georg Trakl (1887–1914), making up a significant part of his lyrical heritage, may be examined through the prism of color and acoustic imagery. The article shows that in his earlier lyric poems (1909–1912) color and sound serve primarily to distinguish between the two spaces, the first of which associates with the reality (natural life, autumn landscape), while the second corresponds to the places of “otherness” (sleep, death). The first space is characterized by a rich palette and sound diversity; the “other” space is depicted mostly in black and white, full of disturbing silence or sharp mechanical sounds. Later verses from 1913–1914 demonstrate less clear distinction of the two spaces, both flow into each other and even merge into one. Color and sound, as it were, “stitch” them through, connecting one with the other. Duality leaves the space and is now concentrated in the very image of autumn, which combines the generosity (abundance of fruits) of the life lived and dying, “black decay.” At the same time, color and sound markers of life and death remain the same, though their use changes slightly: color often acts now as a part of a complex image (“blue wings of the evening”), “dark” tends to become “black”; sounds subside, replaced by a meaningful silence.